Succession of soil microarthropod communities during the aboveground and belowground litter decomposition processes. (July 2017) - Fujii, Saori; Takeda, Hiroshi
Abstract: The process of litter decomposition is driven by interactions among climate, litter quality, and decomposers. However, information about the soil animal community involved in fine-root litter decomposition remains limited. We compared the composition of the soil microarthropods involved in leaf and root decomposition in field experiments using litterbags. To evaluate the relative effects of litter type and initial litter position, we set up a two-factor experiment (litter type × litter position). Litterbags containing either roots or leaves were placed at two positions (either on the soil surface or buried within the soil) and were collected to follow the succession of microarthropods in the decomposing litter for three years. We found different successional patterns of soil microarthropods between the natural processes of leaf and root litter decomposition (i.e. leaves on the soil surface and roots buried within the soil), which were caused by taxonomy-specific responses to both litter quality and litter position. Prostigmata were clearly affected by the stage of litter decomposition; they were initial colonisers of decomposition in all litterbag treatments. The abundances of other taxa were more determined by litter position; however, Oribatida showed a preference for later stages of decomposition, while Collembola and Mesostigmata were strongly determined by water content related to litter position. Although litter quality was not the primary factor controlling their distribution, the ratio of Oribatida to Collembola gradually increased during the decomposition process in the belowground litterbags. Our results indicate that Oribatida are primarily involved in root litter decomposition process, particularly in the late stages of decomposition under natural conditions. Highlights: Knowledge about soil fauna involved in root litter decomposition remains limited. The succession of soil mesofauna was investigated in a litterbag experiment. Faunal successional patterns were different during leaf and root decomposition. More than twice as many soil mesofauna colonised root litter compared to leaf litter. Oribatida were primarily involved in root litter decomposition.